Interactive driver education curriculum (idec) courseware for illiterate user - Syamimi Hazirah, Busro (2013)
Interactive Driver Education Curriculum Courseware for Illiterate User also known as iDEC Courseware is a courseware application about driving education curriculum designed specifically for the illiterate people who have the disabilities to read and write but at the same time, wish to have their own driving license. The main purpose of iDEC Courseware is to help the illiterate people to learn about driver education curriculum in an interactive way. It can also be used by the instructor of a driving institution to deliver the information regarding the Kurikulum Pendidikan Pemandu (KPP) that is related with highway codes and other relevant information. iDEC Courseware consists of a module called Learning Highway Code Module which consists of information regarding the highway code. It is divided into six categories where all the information regarding the driver education curriculum will be presented with the aid of the multimedia elements. It will be implemented with multimedia elements such as text, graphics, audio and video animation in order to help the illiterate people to understand the driver education curriculum in an interactive way.